Using Content-Based Reading Materials for Academic Reading - Martinez Abarca, Sonnia Carlota; Aviles Villon, Gioconda Monserrate; Maruri Orellana, Ana María (RECIMUNDO, 2017)
This text explores the conceptual developments useful as theoretical support to the Project “Metacognitive Strategies in the Teaching and Learning of Reading”, which are related to the notion that reading underlies the work, the strategies (cognitive and metacognitive) and its role in the reading didactics; moreover, some aspects showed are related to the didactic design proposal, the unit didactic, the didactic planning, and the elements that constitute it.